Students’ Conceptions on Circadian and Seasonal Cycles - Weizinger, Sylvia; Hemmer, Ingrid (Journal of Geography Education, 2007)
Every day the change between day and night can be observed. Furthermore, the seasons change during the year at least in the Central European lines of latitude. There is a constant rotation between the warm summers and the cold winters, in which these extreme seasons are superseded by the moderate seasons spring and autumn. In the meantime one can also notice that in December there are people in swimming-suits on the Australian beaches and that in the summer-months of the Northern Hemisphere one can go skiing in the Snowy Mountains. But how are these differences to explain? In Germany pupils start dealing with the topic late in secondary school. Nevertheless, the pupils normally have their own pre-educational concepts which can possibly disturb the learning process at school. According to the theory of conceptual change, a group of 10 to 12 year old Central European students was examined on their pre-curricular conceptions of the circadian and seasonal cycles, a topic which they can observe every day. Furthermore, they were questioned on their ideas of polar night and midnight sun, which they possibly have not yet experienced themselves. The purpose of the study was to show if the pupils have some common misconceptions concerning the above mentioned topics. In addition, it was examined whether wrong ideas can be easily replaced by the scientific facts or if the pupils still prefer using their own conceptions after a geography lesson. Therefore, the students were questioned before and after the lesson, with the result that the pre-educational concepts can be changed into scientific knowledge, though it was easier to make them adopt scientific explanations with topics they had not heard of before.